Eksistensi Masjid Pesisir Di Tengah Badai Covid-19 : (Studi Kasus: Masjid Pasa, Kota Pariaman) - Akdila Bulanov (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
Masjid Pasa is located in the Preparatory Pariaman City. Masjid and strong traditional values ​​are able to compete in the midst of society that has experienced changes due to covid-19. Covid-19 does not rule out the possibility of eliminating the traditional values ​​of the Masjid. Existence can be maintained because of the ability of the Masjid to maintain the elements it has. This study uses a qualitative descriptive method. Data obtained from key informants and supporting informants. The results showed that, Masjid Pasa is still alive today, even though Masjid Pasa is in the midst of a society that has experienced changes and developments due to covid-19. The ability of the Masjid to keep its elements in balance with one another in the midst of modernization is the key to the sustainability of the Masjid.